Violence and schooling - Acevedo Tovar, Luz Marina (2014)
The Institute of Educative Investigations organized, like every year, the annual investigation workshop; this time, October 2009, the subject of the workshop was “school violence”. The event gathered teachers and students, there were presentations in the mornings for three days and in the afternoon they formed groups for dialogue and discussion in order to reach a conclusion and propose suggestions that could represent a contribution and a stimulus for new investigations.